2020
DOI: 10.1016/j.bja.2020.04.067
|View full text |Cite
|
Sign up to set email alerts
|

Front-of-neck airway rescue with impalpable anatomy during a simulated cannot intubate, cannot oxygenate scenario: scalpel–finger–cannula versus scalpel–finger–bougie in a sheep model

Abstract: Background: Front-of-neck airway rescue in a cannot intubate, cannot oxygenate (CICO) scenario with impalpable anatomy is particularly challenging. Several techniques have been described based on a midline vertical neck incision with subsequent finger dissection, followed by either a cannula or scalpel puncture of the now palpated airway. We explored whether the speed of rescue oxygenation differs between these techniques. Methods: In a high-fidelity simulation of a CICO scenario in anaesthetised Merino sheep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 19 publications
3
11
1
Order By: Relevance
“…We chose CICO declaration as the start time to mimic the real-world situation of an unanticipated crisis, during which time is expended as the airway operator works with the team to assemble the necessary equipment for FONA. Our findings are consistent with the results in the only other study comparing the same 2 techniques in simulated impalpable neck anatomy in ovine models, published by Heard et al 10 SFC had a significantly shorter time to first oxygen delivery (hazard ratio, 8.87; 95% CI, 4.31–18.18; P < .001) with higher overall success. Although the time taken from CICO declaration to oxygen delivery was longer in our study, our neck booster was thicker at 5 cm (compared to 3 cm in the above study), and the pliability of synthetic material differs from that of live animal tissue.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We chose CICO declaration as the start time to mimic the real-world situation of an unanticipated crisis, during which time is expended as the airway operator works with the team to assemble the necessary equipment for FONA. Our findings are consistent with the results in the only other study comparing the same 2 techniques in simulated impalpable neck anatomy in ovine models, published by Heard et al 10 SFC had a significantly shorter time to first oxygen delivery (hazard ratio, 8.87; 95% CI, 4.31–18.18; P < .001) with higher overall success. Although the time taken from CICO declaration to oxygen delivery was longer in our study, our neck booster was thicker at 5 cm (compared to 3 cm in the above study), and the pliability of synthetic material differs from that of live animal tissue.…”
Section: Discussionsupporting
confidence: 92%
“…While the fourth National Audit Project (NAP 4) reported a 65% failure rate with the cannula-based technique, 13 our study reported a much lower failure rate with SFC (first-attempt failure, 28%; overall failure, 15%) and higher odds of success compared to SFB. Although consultant grade participants exhibited improved performance in the study by Heard et al, 10 our study found no association between anesthesia experience and time-to-oxygen delivery. A CICO situation requiring an emergency FONA is an extremely rare occurrence; hence, our participants possessed little experience with these techniques.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…The Difficult Airway Society guidelines recommend scalpel-bougie cricothyrotomy, but allude to the use of other valid techniques if additional equipment and comprehensive training are available. 6 Furthermore, while the fourth National Audit Project (NAP 4) reported greater success with surgical techniques over cannula cricothyrotomy, 7 recent animal studies 8,9 have demonstrated the effectiveness of properly performed cannula cricothyrotomy. Notwithstanding this, operators must be mindful of the potential for barotrauma and subcutaneous emphysema associated with inappropriate jet ventilation, which will make subsequent cricothyrotomy attempts difficult or impossible.…”
Section: Discussionmentioning
confidence: 99%
“…The time difference between the performances of the two techniques is in seconds rather than in minutes [69] and it is likely that this small time factor doesn't have any impact on mortality [1]. In a randomized trial involving sheep models, Heard et al [70] demonstrated a better performance in oxygen delivery using the scalpel-finger-cannula technique as compared to scalpelfinger-bougie, when managing a simulated CICO scenario. In another animal study with porcine models, Umek et al [71] compared the success rate of rescue oxygenation (defined as arterial oxygen saturation > 90% 5 min after the beginning of oxygenation) between surgical scalpel-bougie technique and percutaneous cannula technique.…”
Section: Surgical Cricothyroidotomymentioning
confidence: 99%